Generation and detection of OAM signals for radio communications - Cano, Eduardo; Allen, Ben; Qiang Bai; Tennant, Alan (2014 Loughborough Antennas and Propagation Conference (LAPC), 2014)
Orbital angular momentum radio has great potential for radio communications that require high security, spectrum efficiency and a large data rate. However, the performance of such a system, measured in terms of mode errors, is highly dependent on the alignment between the centre of the receiver array and the transmit array boresight. In addition, other impairment phenomena, such as transmit array imperfections, receiver phase errors and thermal noise can considerably degrade the performance of the orbital angular momentum radio system. In this paper, the effects caused by receive array angular and phase errors are evaluated by means of simulations. Furthermore, Monte Carlo simulations are employed to obtain the bit error rate performance of multi-level modulation orbital angular momentum radio systems.